ANAPHORA AND CATAPHORA OF ARGUMENTATITIVE ARTICLES IN INDONESIAN OPINION AND EDITORIAL COLUMN - Rahman, Yenni Arif (Jurnal Akrab Juara, 2019)
The study provides an empirical analysis on the use of anaphora and cataphora in Indonesian opinion and editiorial column. Data for the study were 10 articles collected from 2 leading english-langauge newspapers in Indonesia. Dooley and Levinsohn monograf gives the thorough examples how to analyse cohesive devices in the text. Of 129 sentence-pairs, 122 employs anaphora as reference and the rest, 7 sentence-pairs, uses cataphora. It is also found the dominant use of pronoun as both anaphora and cataphora which contributes 72% or 92 pronouns as reference. The rest are distributed to relative pronoun, nouns, adverbs, and verbs.